The Mechanics of Dualistic Models: "Comparable" Structures and Comparative Statics Results - Ana Paula Martins (Journal of Economics and Political Economy, 2014)
In this paper we present and confront the main comparative static results - effects of labor supply, demand and institutional wage movements - of the (a) basic two-sector model in six different scenarios: free market; partial (one-sector) coverage with perfect intersector mobility; partial (one-sector) coverage with imperfect mobility (Harris-Todaro); multiple (two-sector) coverage with imperfect mobility (Bhagwati-Hamada); partial (one-sector) coverage with affiliation restrictions in the covered sector; partial (one-sector) coverage with limited employment generation ability in the traditional uncovered sector.
Keywords: O15; O18; R23; J42; J61; F22; 330; Migration; Mobility; Minimum Wages; Segmented Labor Markets; Regional Labor Markets